Ethical (and Human) Formation Based on Literary Experience: Contributions of Pedagogical Anthropology to Didactics of Literature - Saavedra Rey, Liliana; Saavedra Rey, Sneider (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This article summarizes classroom research conducted over five years. It analyzes the effect of literary experience on the ethical education and formation (Bildung) of eleventh-grade students. Through the methodology known as lived experience, the study focused on the possible worlds of classic heroism and existentialism as a life-world, approached through a narrative, hermeneutic, and phenomenological lens, within the framework of pedagogical anthropology. The results demonstrated that the didactics of literature can transcend the discursive nature of reading, transforming it into a question of existence. Thus, it is concluded that this literary experience implies for the readers a leap outside of themselves in pursuit of the generality inherent in formation as a potential effect, prompting them to question their identity and decisions in relation to the other and the others represented in fiction.